Comunicação de marketing no varejo para a baixa renda : um estudo de caso do Programa Pinga-Fogo na TV - Cantagallo, Maria Virgínia (2013)
The thematic 'marketing communication' has been addressed in this study within the context of retail marketing and through low income point of view. This is a qualitative exploratory-descriptive research through a case study approach aiming to investigate how communication is constructed within retail marketing for Iow-income Pinga- Fogo na TV Program. To achieve this goal, the study was conducted aiming four objectives: the program description, the characterization of marketing communications, the advertisers positioning and the behavior of consumer audience. Documentary research, interviews and observations were conducted. The data were organized and handled by means aí content analysis, using NVivo9 Qualitative analysis Software. The findings were organized in four sections, according to the proposed goals. Regarding the description of Pinga-Fogo program, it is a live TV program. The content sequences were standardized and non-standardized within the flow. Standardized ones refer to the program opening and closing, while thee non-standardized ones are composed by flow elements: news, announcements, humor, sounds, everyday life problems and dramas. Concerning the characterization of marketing communications, this occurs during the program by means of advertising, sales promotion and merchandising and during commercial breaks through advertising and sales promotion. The marketing mix happens in an integrated and communicative way, and there are more advertisements during the program. In relation lo retail marketing formals which occur in the program, all of them operate with shops and the ones that are mentioned the most are characterized as department stores. Among the categories of products advertised, 'food' category stood out. With regard lo the retail advertisers' positioning. it was investigated (heir positioning about Pinga-Fogo in the TV program and how they expect to position themselves against the consumer. Simplicity and Ieadership were found. About the behavior of the consumer audience, the advertiser broadcasted during the program which was remembered the most was Loja Gaucha store and during the commercial break, it was Bom Dia supermarket. Considering the motivations lo buy. the guarantee of the presenter Pinga-Fogo about the shops and the products advertised was the most frequently mentioned. With respect to shopping experiences, the most mentioned advertiser was Loja Gaucha store. In relation to the payment methods: credit cards, installment credit and in Cash payment stood out. Considering the retail marketing for low-income, the store environment and service were approached and the most important items mentioned were space and quality, respectively.